SPE Rocky Mountain Petroleum Technology Conference 2009
DOI: 10.2118/122793-ms
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Reservoir Simulation Capabilities for Tight Gas Reservoirs

Abstract: It is critical to identify optimum well spacing to develop cost-effective full field development plans for tight gas reservoirs. Accurate prediction of well performance is a major challenge that arises during the development of such reservoirs. Understanding well performance is needed for both well design and depletion planning. Almost all wells in tight gas fields are hydraulically fractured. We have investigated methods of simulating hydraulic fractures using coarse grids since explicitly gridding these frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…A description of prior efforts to apply integrated reservoir modeling to tight gas sands can be found in the literature [3][4][5][6][7] . A common objective mentioned in these papers is the need to define optimum well spacing in thick, tight fluvial systems, and the need to build representative 3D static models with sand body distributions that duplicate reservoir continuity.…”
Section: Integrated Reservoir Modeling Objective: the Search For Optimentioning
confidence: 99%
“…A description of prior efforts to apply integrated reservoir modeling to tight gas sands can be found in the literature [3][4][5][6][7] . A common objective mentioned in these papers is the need to define optimum well spacing in thick, tight fluvial systems, and the need to build representative 3D static models with sand body distributions that duplicate reservoir continuity.…”
Section: Integrated Reservoir Modeling Objective: the Search For Optimentioning
confidence: 99%
“…If one were to artificially adjust gas properties so that fluid mobility term is independent of pressure, then no spatial mobility gradients are introduced for the pressure approach as a result of pressure gradients. In this case, the difference in results between approach and pressure approach is substantially decreased (Abacioglu et al, 2009). …”
mentioning
confidence: 93%
“…Previous research had identified differences of results between a reservoir simulator using the pressure formulation (Eq. 1) and a simulator using pseudopressure formula (Abacioglu et al, 2009).…”
mentioning
confidence: 99%
“…The permeability of this unconventional gas reservoir is less than 0.1mD (Abacioglu, 2009;Pankaj, 2010). Nowadays, different completion measures have been applied to tight gas reservoir, and may lead to different well performance.…”
Section: Introductionmentioning
confidence: 99%